Exploring the Mesenchymal Stem Cell Secretome for Corneal Endothelial Proliferation - Bert Van den Bogerd; Nadia Zakaria; Steffi Matthyssen; Carina Koppen; Sorcha Ní Dhubhghaill (Stem Cells International)
Ex vivo grown human corneal endothelial cells (HCEnC) are a new emerging treatment option to treat visually impaired patients aimed at alleviating the current global donor shortage. Expanding HCEnC is still challenging, and obtaining cells in sufficient quantities is a limiting factor. It is already known that conditioned medium obtained from bone marrow mesenchymal stem cells can stimulate the proliferation of endothelial cells. The aim of this study was to take this work a step further to identify some of the underlying factors responsible. We confirmed the stimulatory effect of the mesenchymal stem cell secretome seen previously and separated the exosomes from the soluble proteins using size exclusion chromatography. We demonstrated the presence of exosomes and soluble proteins in the early and late fractions, respectively, with transmission electron microscopy and protein assays. Proliferation studies demonstrated that growth stimulation could be reproduced with the later protein-rich fractions but not with the exosome-rich fraction. Antibody assays revealed the presence of the secreted proteins EGF, IGFBP2, and IGFBP6 in protein-high fractions, but the growth enhancement was not seen with purified protein formulations. In conclusion, we confirmed the stimulatory effect of stem cell-conditioned medium and have determined that the effect was attributable to the proteins rather than to the exosomes. We were not able to reproduce the growth stimulation, however, with the pure recombinant protein candidates tested. Specific identification of the underlying proteins using proteomics could render a bioactive protein that can be used for ex vivo expansion of cells or as an in vivo drug to treat early corneal endothelial damage.